Analisis Kinerja Keuangan Dengan Metode Common Size Pada PT. Bank Mandiri (Persero) TBK - Rif’ Aida Mirza Aurora; Ashilah Razaktania W; Eva Herwanti; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
financial performance analysis is an important aspect in assessing the stability and operationalefficiency of a company, especially in the banking sector. This research aims to analyze the financialperformance of PT. Bank Mandiri (Persero) Tbk during the 2019-2021 period used the Common Sizemethod. Through a quantitative approach, company balance sheet and income statement data are studiedto identify fluctuations and trends in financial components. The results of the analysis show that there wasa decrease in the cash percentage in 2019, but there was a significant increase in the following years. Inaddition, purchasing government bonds and diversifying investment portfolios are important strategies inoptimizing income and minimizing risks for banks. The distribution of funds, which is reflected in theincrease in the proportion of credit provided, also shows the bank’s ability to carry out its financialintermediation function well, providing a positive impact on economic growth and financing importantsectors.